Sistem Kontrol dan Monitoring Suhu dan Kelembaban GreenHouse untuk Produksi Green Fodder - Alwan J.Ishak; Arifuddin, Rahman; Subairi (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2026)
The high cost of livestock feed and dependence on seasonal forage highlight the need for a more efficient and controlled green fodder corn production system. This study aims to design and implement an Internet of Things (IoT)–based greenhouse control and monitoring system to maintain optimal environmental conditions for green fodder corn production. The system was developed using a Wemos D1 R2 microcontroller integrated with a DHT11 temperature and humidity sensor, a Real Time Clock (RTC) module, fans, a water pump, and grow lights, with Blynk as a remote monitoring platform. Experimental results indicate that the system is able to automatically and stably regulate temperature, humidity, irrigation, and lighting, with average sensor errors of 0.64 °C for temperature and 4.91% for humidity. The novelty of this research lies in the integration of environmental control and scheduled management of green fodder corn growth phases within a simple and practical IoT system, specifically designed to support rapid-harvest forage production in greenhouse environments.